Optimizing the Performance of Satbinmas Through Guidance and Counseling in Preventing Motor Vehicle Theft Crimes in the Jurisdiction of Jepara Police Resort - Agitama, Rafa Rayenda (Advances in Police Science Research Journal, 2024)
Crime refers to behavior or actions that can harm others, disrupt public order and tranquility. Common forms of crime include conventional crimes that involve criminal acts against life, body, property, and mental health, carried out in a conventional way or using new technology. Examples of conventional crimes include motor vehicle theft, which remains one of the crimes that frequently occur in Indonesia. In the effort to prevent motor vehicle theft crimes, the Binmas function has an important role in providing education and knowledge to the public on how to prevent such crimes through guidance and counseling activities. In Jepara Police Resort, motor vehicle theft always becomes a high-level crime every year. In this writing, the author utilizes George R. Terry’s POAC theory (Planning, Organizing, Actuating, and Controlling) to answer the first problem. Additionally, the author also uses the organizational resource theory consisting of 4M, namely, Man, Money, Method, and Material. Using the POAC theory, weaknesses were found in the planning aspect, such as the lack of guidance and counseling materials related to motor vehicle theft. In addition, the vacancy of some positions forced several personnel to take on multiple responsibilities, which resulted in their suboptimal performance. The author recommends that the Satbinmas unit increase their efforts because they are still not optimal. The Satbinmas unit of Jepara Police can propose an increase in personnel, and prioritize guidance and counseling materials related to motor vehicle theft.